Growth of (1 1 1) and (2 0 0) orientation cubic MgZnO thin films under different oxygen flow rate by PLD method and its difference in element composition and optical absorption characteristics. (April 2015) - Han, S.; Shao, Y.K.; Lu, Y.M.; Cao, P.J.; Liu, W.J.; Zeng, Y.X.; Jia, F.; Zhu, D.L.
Graphical abstract: Abstract: Under different migration energy of reactive Mg, Zn and O atoms from MgZnO target at different oxygen flow rate, (2 0 0) and (1 1 1) orientations MgZnO thin films with cubic structure were fabricated on fused quartz substrate by PLD method. And MgZnO thin film possesses relatively higher Zn composition and lower Mg composition when deposited more along (1 1 1) orientation. The band gap and UV absorption characteristics of MgZnO thin film do not change completely in accordance with the Mg/Zn atom ratio of MgZnO thin films deposited at different oxygen flow rate, but influenced more by the ratio between Mg and Zn atoms that combined with O atoms in MgZnO crystal lattice and the grain boundary density of MgZnO thin films deposited at different oxygen flow rate.